Melatonin renders neuroprotection by protein kinase C mediated aquaporin-4 inhibition in animal model of focal cerebral ischemia - Bhattacharya P.; Pandey A.K.; Paul S.; Patnaik R. (My University, 2025)
Aim: Aquaporin-4(AQP4) expression in the brain with relation to edema formation following focal cerebral ischemia was investigated. Studies have shown that brain edema is one of the significant factors in worsening stroke outcomes. While many mechanisms may aggravate brain injury, one such potential system may involve AQP4 up regulation in stroke patients that could result in increased edema formation. Post administration of melatonin following ischemic stroke reduces AQP4 mediated brain edema and confers neuroprotection. Materials and methods: An in-silico approach was undertaken to confirm effective melatonin-AQP4 binding. Rats were treated with 5 mg/kg, i.p. melatonin or placebo at 30 min prior, 60 min post and 120 min post 60 min of middle cerebral artery occlusion (MCAO) followed by 24 h reperfusion. Rats were evaluated for battery of neurological and motor function tests just before sacrifice. Brains were harvested for infarct size estimation, water content measurement, biochemical analysis, apoptosis study and western blot experiments. Key findings: Melatonin at 60 min post ischemia rendered neuroprotection as evident by reduction in cerebral infarct volume, improvement in motor and neurological deficit and reduction in brain edema. Furthermore, ischemia induced surge in levels of nitrite and malondialdehyde (MDA) were also found to be significantly reduced in ischemic brain regions in treated animals. Melatonin potentiated intrinsic antioxidant status, inhibited acid mediated rise in intracellular calcium levels, decreased apoptotic cell death and also markedly inhibited protein kinase C (PKC) influenced AQP4 expression in the cerebral cortex and dorsal striatum. Significance: Melatonin confers neuroprotection by protein kinase C mediated AQP4 inhibition in ischemic stroke. © 2014 Elsevier Inc. All rights reserved.